Regulating random mechanical motion using the principle of auto-winding mechanical watch for driving TENG with constant AC output – An approach for efficient usage of high entropy energy. (September 2021) - He, Gaofa; Luo, Yingjin; Zhai, Yuan; Wu, Ying; You, Jing; Lu, Rui; Zeng, Shaokun; Wang, Zhong Lin
Abstract: The world is fulfilled with low-quality, irregular, and widely distributed energy, but highly efficient harvesting of such high-entropy energy is hardly possible due to the limitation of currently existing technologies. Recently, triboelectric nanogenerators (TENGs) were invented to harvest random and ambient mechanical energy, and have shown wide applications because of their high efficiency and low-cost. However, the output of the TENG is dictated by the irregularity of the input mechanical agitation. This paper reports a mechanical regulator using the principle of auto-winding mechanical watch for driving the triboelectric nanogenerator with constant AC output (Constant Output TENG, CO-TENG). The device which comprised energy harvest and storage module, energy controllable release module, and energy conversion module can achieve energy harvesting-storage-release not only steadily but also continually under even low-frequency (0.5 Hz) and random working stimulation. The CO-TENG has been successfully applied to harvest the energy of random waves, wind, and water flows, through the adjustment of the input gear train and energy collection parts, such as water turbine, wind scoop, and oscillating buoy. The CO-TENG can steadily and continually produce an open-circuit voltage of 550 V, a short-circuit current of 6 μA, and transferred charges of 190 nC under low-frequency and random mechanical stimulation. With the rectifier filter, a commercial thermometer and 450 LEDs in serial connection were separately powered by the CO-TENG. It demonstrates that the CO-TENG is a potential solution for effective usage of high entropy energy that has a random amplitude and irregular low-frequency. Graphical Abstract: The paper reports a mechanical regulator using the principle of auto-winding mechanical watch for driving the triboelectric nanogenerator, which can steadily and continually release electric energy without manual intervention under random and low-frequency conditions, such as random waves, wind, and water flows. ga1 Highlights: A mechanical regulator is proposed which is using the principle of auto-winding mechanical watch for driving the TENG. The device can steadily and continually produce AC output under random and low-frequency excitation. An escapement was designed to control release of energy, with reference to the working principle of mechanical watches.